Evaluation of Open Pollinated Normal Maize Varieties in the Eastern Mid Hill of Nepal - Sah, Surya N.; Sharma, Diwakar (Nepal Agriculture Research Journal, 2014)
Full season maize genotypes were evaluated in on station coordinated varietal experiments during summer season at Agriculture Research Station (ARS), Pakhribas in three consecutive years 2003, 2004 and 2005. The experiments were laid out in randomized complete block design (RCBD) with three replications. The objective of this study was to identify high yield potential normal maize genotypes suitable for the existing cropping patterns in the eastern mid hill. Genotypes were evaluated in coordinated varietal trials (CVT) in 2003, 2004 and 2005 and in intermediate yield trial (IYT) in 2004. Five common genotypes including local and standard check were evaluated in the CVT 2003 and in the CVT 2004, another five common genotypes tested in the CVT 2004 and in the CVT 2005 and six common genotypes of the IYT 2004 and CVT 2005 were analyzed over year. Genotype P501-SARCO-F1/P502-SARCO-F1 produced significantly higher grain yield followed by DRACOSYN- F1/DRBCOSYN-F1 in the 1st two years and found about one week earlier than Mankamana-3. Across 00502 and Across 9942/Across 9944 were found superior with respect to grain yield and phenotypic characters like husk cover, plant aspect and ear aspect both in CVT 2005 and IYT 2004 across the years and the genotype Across 9942/Across 9944 was found tolerant to turcicum leaf blight (TLB) in 2005. Nepal Agric. Res. J. Vol. 8, 2007, pp. 18-22 DOI: http://dx.doi.org/10.3126/narj.v8i0.11566